Stigmatized Attitude toward Mental Illness among the Caregivers of Patients with Psychiatric Illness - Bhutia, Tenzing Dolkar; Palagiri, Mary Madhvi; Sequeira, Flavia; Jose, Gini; MC, Anil; Rodrigues, Lavina (Journal of Health and Allied Sciences NU, 2022)
Background: Stigma is a trait, belief, or disgrace where a mentally ill person is socially defamed in certain manners. Stigma can cause great psychological distress among the caregivers of patients with psychiatric illness.Aim: The study was aimed to assess the level of stigmatized attitude toward mental illness among the caregivers.Materials and Methods: A cross-sectional study design was used to collect data among 210 caregivers of patients with psychiatric illness who were recruited using purposive sampling technique. Baseline proforma and stigmatizing attitude scale were used to collect the data.Results: The findings depicted the mean age of the caregiver was 44 years. More than half number of subjects (54.3%) were females. Majority (90.44%) of the caregivers had moderate, whereas 3.33% had low stigmatizing attitude with the mean ± standard deviation was 52.77 ± 9.91. Chi-squared test showed no significant association between stigmatized attitude score and selected demographic variables.Conclusion: It is vital that awareness programs and antistigma campaign can be initiated in the community settings, with the help of interdisciplinary coordination and collaboration of the health care members to eradicate the stigmatizing attitude among the caregivers.
Keywords: caregivers; stigma; stigmatized attitude; stigmatization; mentally ill patients; psychiatric illness.